Studies of Non-Stationary Temperature Regime of Frozen Dams Made of Local Materials on Permafrost Foundations (Issledovaniia Nestatsionarnogo Temperaturnogo Rejima Zamorojennkh Plotin ez Mestnkh Materialov na Vechno-Merzlkh Osnovabikh) - Ukhova,N V (1977)
The specific characteristics of hydraulic engineering construction on permafrost foundations under harsh climatic conditions result in a situation in which the most economic type of dam in the regions is the type made of local materials. A distinction can be made between two methods of constructing dams from local materials on permafrost foundations: the 'warm' method, used when construction takes place primarily during the summertime by usual methods, and usually encountered in regions with moderate climates, and 'cold,' when construction takes place in winter with stratified freezing of the entire dam or its dividual elements, or in summer, with subsequent freezing of the structure. The frozen part of the dam is intended to make it impermeable to water. Reliable operation of partly or completely frozen dams is determined by the temperature regime of the construction and the foundation, which must be such that the frozen 'curtain' in the dam does not thaw out during the latter's operation. The dissertation is devoted to an analytical experimental study of the nonstationary temperature regime of frozen dams made of local materials on permafrost foundations, and constitutes one aspect of the problem of construction of dams on permafrost foundations, analyzed by the group of coworkers of the department under the leadership of Corresponding Member of the Academy of Sciences of the USSR, Doctor of Technical Sciences, Professor N. A. Tsytovich. Trans. of Mono., Moscow 18p, 1967.